2022
DOI: 10.1128/mbio.01250-22
|View full text |Cite
|
Sign up to set email alerts
|

Secreted in a Type III Secretion System-Dependent Manner, EsaH and EscE Are the Cochaperones of the T3SS Needle Protein EsaG of Edwardsiella piscicida

Abstract: Edwardsiella piscicida causes severe hemorrhagic septicemia in fish. Inactivation of the type III secretion system (T3SS) increases its 50% lethal dose (LD 50 ) by ~10 times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…As E. piscicida possesses virulence factors (VFs) similar to many intestinal pathogens, such as Flagella, adherence, invasion, type III and type VI secretion systems (T3SS and T6SS), quorum sensing (QS) regulators, iron uptake, two-component systems (TCS), toxins, and invasion proteins (1)(2)(3), it could be used as an attractive model organism to study the role of a single VF or a combination of VFs in pathogenic process (1)(2)(3). Unfortunately, current researches have mainly focused on revealing the functional mechanisms of single VFs in E. piscicida-induced diseases in mammals (1,4,5); the related research in fish is limited. Therefore, exploring the potential mechanisms underlying the mutual interaction of VFs to induce deep infection may not only enrich the knowledge of E. piscicida-induced enteritis in fish but also provide theoretical references for development of optimal strategies for the control and prevention of such diseases.…”
Section: Introductionmentioning
confidence: 99%
“…As E. piscicida possesses virulence factors (VFs) similar to many intestinal pathogens, such as Flagella, adherence, invasion, type III and type VI secretion systems (T3SS and T6SS), quorum sensing (QS) regulators, iron uptake, two-component systems (TCS), toxins, and invasion proteins (1)(2)(3), it could be used as an attractive model organism to study the role of a single VF or a combination of VFs in pathogenic process (1)(2)(3). Unfortunately, current researches have mainly focused on revealing the functional mechanisms of single VFs in E. piscicida-induced diseases in mammals (1,4,5); the related research in fish is limited. Therefore, exploring the potential mechanisms underlying the mutual interaction of VFs to induce deep infection may not only enrich the knowledge of E. piscicida-induced enteritis in fish but also provide theoretical references for development of optimal strategies for the control and prevention of such diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The abundance of proteins in the type VI secretion system (T6SS), type III secretion system (T3SS), and flagellum system was downregulated (Figure ). Previous studies have demonstrated that the chaperone protein EscE interacts with the apparatus EsaH and EsaG (a T3SS needle protein) and that EscE and EsaH are cochaperones of EsaG . EseC inhibits biofilm formation by sequestering the chaperone EseE .…”
Section: Resultsmentioning
confidence: 99%
“…EseC inhibits biofilm formation by sequestering the chaperone EseE . EscA and EseE are cochaperones of EseC, and EseE promotes its secretion. , The disordered region of the T6SS effector EvpP is essential for EvpC binding . FilC and FliC are flagellar filament components associated with the ability of bacteria to swim .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation